A failure analysis of the cylinder and connection bolts in a buoyancy regulator of an underwater glider. (July 2023) - Yang, Chiye; Guo, Liming; Liu, Jing; Pan, Guang
Highlights: A failure analysis of the cylinder in a buoyancy regulator of an underwater glider is proposed. The effects of the ovality on the cylinder sealing performance and health are analyzed. A failure analysis of the connection bolts in in a buoyancy regulator of an underwater glider is proposed. The effect of the thickness and size of bolts on the load capacity of the connection bolts are analyzed. Abstract: The buoyancy regulator is key device used in underwater gliders for adjusting their buoyancy. This paper studies the failures of the cylinder and the connection bolts during the working processing of the buoyancy by using a finite element method. The effect of the ovality on the sealing and the scratching failures of the cylinder is analyzed. Note that the poor machining accuracy should produce the cylinder sealing and the scratching failures. Some suggestions for improving the ideal cylinder design are introduced. Additionally, the specific reasons of the failures of the connecting bolts for the buoyancy regulator are also investigated. Note that the overload causes the failures of the connection bolts. The loading capacity can be increased by making the connecting flange stiffer or by utilizing the larger bolts. The optimization design methods for the piston and the piston rod are provided according to the simulation results. This paper can provide a failure analysis and structural optimization method for the buoyancy regulators.